Knowledge and practices regarding standard precautions among supportive staff in the National Hospital of Sri Lanka - Mathangasinghe, Yasith (Sri Lanka Journal of Surgery, 2020)
Introduction: Adherence to standard precautions significantly reduces the transmission of hospital-acquired infections. We intended to assess the knowledge and practices regarding standard precautions among supportive staff members in the National Hospital of Sri Lanka (NHSL). Methods: A descriptive cross-sectional study was conducted among supportive staff members at NHSL. They were selected using stratified one-stage cluster sampling and their knowledge and practices regarding standard precautions were assessed using an interviewer-administrated questionnaire. Results: Of 108 participants, 69 (63.9%) were aged 20-40 years. One-hundred and five (97.2%) were educated up to Ordinary Level and 48 (44.4%) had working experience of more than six years. Twenty-six had at least one needle-stick injury during their career. Six (5.6%) have not been vaccinated for Hepatitis B since their recruitment. Mean knowledge and practice scores were 66.3±12.5% and 70.0±7.7% respectively. There were no differences in knowledge scores based on the level of education (t=1.19, p=0.24) and the total years of service (t=- 0.44, p=0.66). Similarly, there were no differences in practising proper precautions based on their educational level (t=0.25, p=0.80) or the duration of service (t=0.87, p=0.39). However, the knowledge score positively correlated with the good practice score (r=0.197, p= 0.04). Conclusions: The supportive staff members with good knowledge were more adherent to the correct practice. Neither the level of education nor the experience was associated with their knowledge or good practices. Provided the potential risk of transmission of blood-borne infections, Hepatitis B vaccination and post-vaccination antibody testing could be made mandatory before starting their carrier.
Keywords: Standard precautions; hospital acquired infections; health care workers; knowledge; practices